Efficacy and safety of two fixed-dose combinations of S-amlodipine and telmisartan (CKD-828) versus S-amlodipine monotherapy in patients with hypertension inadequately controlled using S-amlodipine monotherapy: an 8-week, multicenter, randomized, double-blind, Phase III clinical study - Ihm SH; Jeon HK; Cha TJ; Hong TJ; Kim SH; Lee NH; Yoon JH; Yoon NS; Hwang KK; Jo SH; Youn HJ (Dove Medical Press, 2016)
Sang-Hyun Ihm,1 Hui-Kyung Jeon,1 Tae-Joon Cha,2 Taek-Jong Hong,3 Sang-Hyun Kim,4 Nae-Hee Lee,5 Jung Han Yoon,6 Namsik Yoon,7 Kyung-Kuk Hwang,8 Sang-Ho Jo,9 Ho-Joong Youn1 1Division of Cardiology, Department of Internal Medicine, The Catholic University of Korea, Seoul, 2Division of Cardiology, Department of Internal Medicine, Kosin University College of Medicine, 3Division of Cardiology, Department of Internal Medicine, Pusan National University Hospital, Busan, 4Division of Cardiology, Department of Internal Medicine, Boramae Medical Center, Seoul National University College of Medicine, Seoul, 5Department of Cardiology, Soonchunhyang University Hospital, Bucheon, 6Division of Cardiology, Wonju College of Medicine, Yonsei University, Wonju, 7Department of Cardiology, Chonnam National University Hospital, Gwangju, 8Department of Internal Medicine, Chungbuk National University, College of Medicine, Cheongju, 9Division of Cardiology, Hallym University Sacred Heart Hospital, Hallym University College of Medicine, Anyang, South Korea Purpose: To evaluate the blood pressure (BP) lowering efficacy and safety of CKD-828, a fixed-dose combination of S-amlodipine (the more active isomer of amlodipine besylate, which is calcium channel blocker) and telmisartan (long acting angiotensin receptor blocker), in patients with hypertension inadequately controlled with S-amlodipine monotherapy.Patients and methods: Eligible patients (N=187) who failed to respond after 4-week S-amlodipine 2.5 mg monotherapy (sitting diastolic blood pressure [sitDBP] ≥90 mmHg) to receive CKD-828 2.5/40 mg (n=63), CKD-828 2.5/80 mg (n=63), or S-amlodipine 2.5 mg (n=61) for 8 weeks. The primary efficacy endpoint, mean sitDBP change from baseline to Week 8, was compared between the combination (CKD-828 2.5/40 mg and CKD-828 2.5/80 mg) and S-amlodipine monotherapy groups. The safety was assessed based on adverse events, vital signs, and physical examination findings.Results: After the 8-week treatment, changes in sitDBP/systolic BP (SBP) were -9.67±6.50/-12.89±11.78, -10.72±6.19/-13.79±9.41, and -4.93±7.26/-4.55±11.27 mmHg in the CKD-828 2.5/40 mg (P<0.0001/P<0.0001), CKD-828 2.5/80 mg (P<0.0001/P<0.0001), and S-amlodipine 2.5 mg (P<0.0001/P=0.0027) groups, respectively, which were all significant BP reductions. At Week 8, the CKD-828 2.5/40 mg (sitDBP/SBP: P=0.0002/P<0.0001) and CKD-828 2.5/80 mg (sitDBP/SBP: P=0.0001/P<0.0001) showed superior BP-lowering effects to S-amlodipine 2.5 mg (P<0.001). At Week 4, all groups showed significant antihypertensive effects but both CKD-828 combinations (CKD-828 2.5/40 mg and CKD-828 2.5/80 mg) exhibited superior BP-lowering effects to that of S-amlodipine 2.5 mg (sitDBP/SBP: P=0.0028/P=0.0001 and P<0.0001/P=0.0012, respectively). The adverse event incidence was significantly lower in the CKD-828 2.5/40 mg (9.52%, P=0.0086) than in the S-amlodipine 2.5 mg group (27.87%) and increasing the telmisartan dose induced no unexpected adverse events, suggesting the safety of CKD-828.Conclusion: CKD-828 is an effective and safe option for patients with inadequate responses to S-amlodipine monotherapy. Keywords: blood pressure, antihypertensive, calcium channel blocker, angiotensin receptor blocker, efficacy, safety